Governança e avaliação dos indicadores socioambientais do Parque Ecológico Diva Paim Barth da cidade de Toledo-PR - Fiori, Angélica (2020)
Urban parks are of great importance for cities, as they have aesthetic, ecological, leisure and recreation functions, in addition to the conservation of the city's natural systems. This research had the identification of identifying the Diva Paim Barth Ecological Park, in the municipality of Toledo, state of Paraná, it contains elements that subsidize the performance of the conservation and public use functions and there is conciliation between these functions, through the use of the PEIR Matrix and environmental indicators, verifying the ways of using and managing the environment. Some flaws were identified during the work related to their use, disposal of hazardous waste and afforestation was the indicator of greatest influence. In the Participative Master Plan 2050, there are no proposals for the park, only that it is in a continuous process of complementation, improvements and adaptations. Environmental education is shown as the key piece in the preservation issue, since it is possible to create activities that develop the environmental awareness of the population, making the space used in the best way, promoting learning and awareness.